Evaluación mecánica de casetónes armables y recuperables fabricados en plástico reciclado (PET, HDPE, LDPE Y COMBINADO) para losas aligeradas (2022)
The lightened slabs use different types of elements for lightening in various materials such as expanded polystyrene and wood with canvas, in order to fulfill their main function. At present it is necessary to look for different actions to recycle and reuse those singleuse plastics that affect different ecosystems in the world, for this reason the design and construction of a that is buildable and recoverable made of recyc coffers led plastic is carried out, for the lightweight slab construction. When carrying out the tests in the laboratory, it was possible to observe that the coffers with the best mechanical properties is the one made with the combination of 10% LDPE, 10% PET and 80% HDPE, since it is the one that supports the most in the ultimate load and deformation presents the least compared to conventional ones such as expanded polystyrene and canvas wood